Honeycomb - Harris, Joanne, 1964- (Saga Press, 2021)
"The toymaker who wants to create the perfect wife; the princess whose heart is won by words, not actions; the tiny dog whose confidence far outweighs his size; and the sinister Lacewing King who rules over the Silken Folk. These are just a few of the weird and wonderful creatures who populate Joanne Harris's first collection of fairy tales"--